In CKD, the kidney failure risk equation predicted 2-y risk for ESKD better than eGFR alone - Aguilar-Ramirez, D; Herrington, WG (American College of Physicians, 2022)
Bundy JD, Mills KT, Anderson AH, et al. Prediction of end-stage kidney disease using estimated glomerular filtration rate with and without race: a prospective cohort study. Ann Intern Med. 2022;175:305-13. 35007146.